Isolation and Identification of the Major Chemical Compounds Found in the Oleoresin Obtained from the Pistachia atlantica Tree (PersianTurpentine Tree, Desf. Subsp. Kurdica) Grown in Ilam Province of Iran - Gharib Naseri, Nahid; Ashnagar, Alamdar; Naghdi, Naserollah (Asian Journal of Chemistry, 2010)
Oleoresin collected after tapping the trunk of the Pistachia atlantica tree grown wild in Ilam province of Iran at the end of spring and the earlier months of summer at intervals was dried and powdered. Water-distilled/Soxhlet extraction of the powdered oleoresin gave an essential oil. TLC and column chromatography (silica gel as stationary phase and methylene chloride as mobile phase) resulted in the separation of three components with Rf = 0.23, 0.48 and 0.92 which were identified as β-caryophylline, spiro[4,5]decane-6-methylene and β-pinene, respectively. The essential oil was analyzed by GC-MS which showed the following nine major components: α-pinene, camphene, β-pinene, bicyclo[3.1.1] hepta-3-ene-2-ol-4,6,6-trimethyl; 1,4-cyclo- hexadiene-1-methanol-4-(1-methyl- ethyl); bicyclo[3.1.1]hepta-3-ene-2-one-4,6,6-trimethyl; β-caryophylline and spiro[4,5]decane-6-methylene.